Evaluation of the risk of acute kidney injury with the use of piperacillin/tazobactam among adult critically ill patients - Mohamed O. Saad (11659429) (2020)
Purpose Piperacillin/tazobactam (PT), when combined with vancomycin, is associated with an increased risk of acute kidney injury (AKI). It is not known whether PT alone is associated with a higher incidence of AKI compared to other β-lactams among critically ill patients. The objective of this study was to compare the incidence of AKI associated with the use of PT to other β-lactams among adult critically ill patients Methods This retrospective study was conducted in the surgical and the medical intensive care units at two hospitals within Hamad Medical Corporation (HMC) in Qatar and included adult critically ill patients who received at least one dose of anti-pseudomonal β-lactams. The primary outcome was acute kidney injury, defined using the Kidney Disease Improving Global Outcomes (KDIGO) criteria. Multiple logistic regression with adjustment for pre-specified potential confounders was used for the primary outcome analysis. Results A total of 669 patients were included in the analysis: 507 patients in the PT group and 162 patients in the control (meropenem/cefepime) group. AKI occurred in 136 (26.8%) members of the PT group and 38 (23.5%) members of the control group [odds ratio (OR) 1.2; 95% confidence interval (CI) 0.79–1.8]. The results were not significantly altered after adjusting for the pre-specified potential confounders (adjusted OR 1.38; 95% CI 0.88–2.15). Conclusion In this study, PT was not associated with a higher risk of AKI compared to cefepime or meropenem among adult critically ill patients. Other Information Published in: Infection License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s15010-020-01480-x